Russlands Angriffskrieg gegen die Ukraine Zeitenwende für die deutsche Sicherheitspolitik - Hansen, Stefan; Husieva, Olha; Frankenthal, Kira (ISPK-Studien zur Konfliktforschung, 2022)
The Russian war of aggression against Ukraine represents a turning point in German foreign and security policy, which requires a complete redefinition of Germany's role within the future European security order. Through contributions by renowned experts, this anthology provides information on the causes of, developments in and so far foreseeable consequences of the Russian war of aggression, systematically examines Germany's policy towards Russia since 1990, provides ideas for new directions in German security policy and explains why timely policy corrections are necessary in order for Germany to be better prepared for future conflict escalations and security policy challenges.